O MODELO CORPORATIVO DE GESTÃO DO CONHECIMENTO E A SUA APLICAÇÃO NAS PRÁTICAS DESENVOLVIDAS POR UNIDADES DE NEGÓCIO: O CASO DE UMA UNIDADE DE NEGÓCIO DE GRANDE PORTE DE UMA COMPANHIA DE PETRÓLEO. - Sacconi, Bruno (2010)
This research aim is to identify knowledge management initiatives in a large Business Unit of an oil company and evaluate the implementation of the corporate model in the identified practices. In this regard, questionnaires with the assumptions of the corporate model were developed and applied to all participants of the projects and their coordinators. The research focused on three projects developed in the research unit comprising three coordinators and 341 participants. After conducting the research and analysing the results, we reach the conclusion that the knowledge management projects developed in the Business Unit have 'partial application' of the premises specified in the corporate model, not meaning thereby that the projects are dissonant, but that each project focuses on different assumptions in the model.